Utveckling av butiksinredning för dagligvaruhandeln : Inbyggnad till potatishiss, löklåda, bakpotatislåda, diverse tillbehör och produktställ - Andersson, Ida; Gode, Katarina (2011)
This master thesis for the Industrial Engineering Design Program at LTU has been made during 20 weeks in 2010-2011 in co-operation with Grafix Inredning AB, a company which design systems for merchandising for shops and public environments. The assignment of the thesis was to develop shop interior for the general dealer, more exactly an enclosure for potato dispensers, a case for onion, a case for baked potato, accessories for the root crop department and product racks. Grafix feels the need to develop both their root crop system and their product racks since they would like to take market shares in these areas. A new shape and function of the root crop system needs to be developed as well as new product racks to spread their supply of these.A pre-study was made with interviews with the person responsible of purchasing shop interior, shop assistants and customer in four general dealers in Luleå. This was made to investigate the current situation in the shops and what is important for the different groups when it comes to the root crop system and product racks. The results from the interviews are that the interior of the root crop system should be simple, rational, easily cleaned and fresh. The product racks should be simple, rational, modern, flexible and invitingly. The results of the pre-study together with demands and wishes from Grafix laid the ground to a specification of requirements. To better understand the meaning of some of the words that the products should express, a workshop was carried out with focus on understanding the words simple, modern, flexible and inviting. Some of these words were qualities that Grafix wanted their products to express, and some words the group found meaningful in the context.The project stepped into a creative phase where many solutions and ideas were developed using creative methods and with the inspiration from the moodboard made in the workshop. The selection was made in collaboration with Grafix and by using a concept scoring matrix to calculate which solution that ...